El control interno y su incidencia en la rentabilidad de la compañía Servipaxa S.A, cantón Quevedo, periodo 2012 - Jácome Martínez, Nathaly Lorena (2015)
Whereas internal control is a topic of discussion by the management of the company Servipaxa SA Quevedo city over the past two years have seen the need for this research work, in order to be useful in decision-making by management in seeking to assess the profitability of the company, compliance with laws, efficient performance of operations and determine whether the financial information is reliable. This theme: "THE INTERNAL CONTROL AND ITS IMPACT ON THE COMPANY PERFORMANCE SERVIPAXA SA, CANTON QUEVEDO, PERIOD 2012". This work is based on the study of internal control, for which we use the COSO II and the study of each of the constituent components such as: control environment, objective setting, event identification, risk assessment, Risk response, control activities, information and communication, monitoring. To run our research we used a methodology in which the different materials and research methods such as analytical and systematic, along with the types of exploratory and descriptive research are detailed, including techniques and instruments include the questionnaire and interview served to the staff of the aforementioned entity to provide information in order to find solution to the issue. That is why, I believe that this work will be useful in the search for possible solutions for the operations of the company. At the conclusion of the research work and after having met the objectives, he reached the following conclusions; company accounting differences between higher yields relative to the physical information module and an increase of 14.89%, a confidence level of 51.25% and regular moderate moderate risk level of 48.75% in terms of the efficiency and effectiveness of operations and in terms of compliance with laws and regulations if the company complies with the various regulations implemented by the control entities.